2004
DOI: 10.1111/j.1365-2036.2004.02082.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐tumour effects of nobiletin, a citrus flavonoid, on gastric cancer include: antiproliferative effects, induction of apoptosis and cell cycle deregulation

Abstract: SUMMARYAim: To demonstrate the antitumour effects of nobiletin (5,6,7,8,3¢,4¢-hexamethoxyflavone), a citrus flavonoid extracted from Citrus depressa Hayata, on human gastric cancer cell lines TMK-1, MKN-45, MKN-74 and KATO-III. Materials and methods: 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay, the TdTmediated dUTP biotin nick-end labelling (TUNEL) method and cell-cycle analysis revealed that nobiletin acted on these cells in several ways, namely by direct cytotoxicity, induction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(73 citation statements)
references
References 29 publications
3
69
0
1
Order By: Relevance
“…Loss of cell viability at low doses was found to be a consequence of apoptosis (Yoshimizu et al 2004 ) . A screening of 78 citrus species showed inhibitory effects of the Epstein-Barr virus antigen (EBV-EA) activation, indicating that citrus phytochemicals may inhibit susceptibility factors involved in the events leading to the development of cancer (Iwase et al 1999 ) .…”
Section: Cancer Chemoprevention Potentialmentioning
confidence: 99%
“…Loss of cell viability at low doses was found to be a consequence of apoptosis (Yoshimizu et al 2004 ) . A screening of 78 citrus species showed inhibitory effects of the Epstein-Barr virus antigen (EBV-EA) activation, indicating that citrus phytochemicals may inhibit susceptibility factors involved in the events leading to the development of cancer (Iwase et al 1999 ) .…”
Section: Cancer Chemoprevention Potentialmentioning
confidence: 99%
“…Nobiletin has been observed to be cytotoxic by modulating cell cycle on TMK-1, MKN-45, MKN-74, and KATO-III human gastric carcinoma cells (Yoshimizu et al, 2004). Another study showed that the compound induced G1 phase arrest on MDA-MB-435, MCF-7, and HT-29 cells (Morley et al, 2007).…”
Section: Effect On Cell Cycle Regulationmentioning
confidence: 99%
“…Tangeretin was also able to induce apoptosis on HL-60 human promyelocytic leukemia cells . While nobiletin, another flavonoid obtained from C. reticulata peels, has been observed to be cytotoxic not only through modulating cell cycle, but also by inducing apoptosis on TMK-1, MKN-45, MKN-74, and KATO-III human gastric carcinoma cells (Yoshimizu et al, 2004).…”
Section: Effect On Apoptosismentioning
confidence: 99%
“…Lee et al [92] revealed that PMFmediated induction of GADD45α partially underlies the anti-proliferative effect of PMF on colorectal cancer cells. Nobiletin was found to act as an anti-carcinogenic compound through anti-proliferative activity, induction of apoptosis and cell cycle deregulation [93]. It was reported that tangeretin suppressed breast cancer proliferation by up-regulating p53/p21 proteins and inducing G1/S phase cell cycle arrest [94].…”
Section: Anti-proliferationmentioning
confidence: 99%